Influência do processo de deposição HVOF com combustível líquido e gasoso na resistência ao desgaste de revestimentos de carboneto de tungstênio com diferentes teores de cobalto - Lamana, Murilo Sérgio (2017)
This work has as main objective the study of the wear resistance of two different tungsten carbide coatings with cobalt matrix (WC-Co) deposited by different HVOF deposition processes. Wear is present in several industrial applications, occurring in many ways and in a variety of environments, such as abrasion (particle contact), erosion (particle impact) and cavitation (bubble implosion). One of the most used methods in the repair is thermal spraying, with the deposition of coatings that promote improvements in the superficial properties of equipments. Among these processes, HVOF (high velocity oxy-fuel) deposition is widely used because its practicality and quality of the results, with a good adhesion between the lamellae, resulting in wear resistant coatings. This process is widely used for the deposition of WC-Co coatings since these have an interesting behavior when it comes to wear, combining properties such as high hardness and high fracture toughness. To evaluate the behavior of these coatings in different wear situations, cavitation, abrasion and erosion tests were performed according to ASTM standard on WC-12Co and WC-17Co coatings, in order to verify the influence of the binder content on the microstructural characteristics, mechanical properties and wear resistance. These coatings were deposited by two different HVOF deposition processes; varying the fuel used between liquid and gaseous. The in situ monitoring of the tensions present in the sample was used during the deposition, to study its influence on the mechanical properties and consequent resistance to wear. The worn surfaces were analyzed by optical profilometry and scanning electron microscopy, to verify the wear present in each situation. It was found that, in general, the deposition process influenced the formation of the residual stresses present in the samples and their microstructural characteristics, with higher velocities for liquid fuel, and higher temperatures for the gaseous fuel. The highest values of hardness and fracture toughness were observed for liquid fuel deposition. These different aspects affected directly the resistance to different types of wear, and the WC-17Co coating deposited with liquid fuel was the most resistant to abrasive and cavitation wear due to the presence of more compressive residual stresses. For erosive wear, the WC-12Co coating deposited by liquid fuel presented higher resistance, due to the higher amount of carbides and lower binder content.